Altered gene expression and functions of mitochondria in human nephrotic syndrome - Holthöfer, Harry; Kretzler, Matthias; Schaegger, Hermann; Kriz, Wilhelm; Kerjaschki, Dontscho; Schlöndorff, Detlef (The FASEB journal, 1999)
The molecular basis of glomerular permselectivity remains largely unknown. The congenital nephrotic syndrome of the Finnish type (CNF) characterized by massive proteinuria already present but without extrarenal symptoms is a unique human disease model of pure proteinuria. In search of genes and pathophysiologic mechanisms associated with proteinuria, we used differential display-PCR to identify differences in gene expression between glomeruli from CNF and control kidneys. A distinctly underexpressed PCR product of the CNF kidneys showed over 98% identity with a mitochondrially encoded cytochrome c oxidase (COX I). Using a full-length COX I cDNA probe, we verified down-regulation of COX I mRNA to 1/4 of normal kidney values on Northern blots. In addition, transcripts of other mitochondrially encoded respiratory chain complexes showed a similar down-regulation whereas the respective nuclearly encoded complexes were expressed at comparable levels. Additional studies using histochemical, immunohistochemical, in situ hybridization, RT-PCR, and biochemical and electron microscopic methods all showed a mitochondrial involvement in the diseased kidneys but not in extrarenal blood vessels. As a secondary sign of mitochondrial dysfunction, excess lipid peroxidation products were found in glomerular structures in CNF samples. Our data suggest that mitochondrial dysfunction occurs in the kidneys of patients with CNF, with subsequent lipid peroxidation at the glomerular basement membrane. Our additional studies have revealed similar down-regulation of mitochondrial functions in experimental models of proteinuria. Thus, mitochondrial dysfunction may be a crucial pathophysiologic factor in this symptom. - Holthöfer, H., Kretzler, M., Haltia, A., Solin, M.-L., Taanman, J.-W., Schägger, H., Kritz, W., Kerjaschki, D., Schlöndorff, D. Altered gene expression and functions of mitochondria in human nephrotic syndrome.
Gesehen am 11.09.2017